Fungsi dan Kewenangan OJK dalam Pengawasan Kesehatan Bank - Samuel, Yoseph; Kardinata, Henes; Hutauruk, Reymond (Universitas Batanghari Jambi, 2024)
One of the key aspects examined is the OJK's authority to take preventive and corrective action against banks that show signs of unsoundness. This analysis provides an in-depth understanding of the effectiveness of the regulatory and supervisory measures taken by the OJK to protect the interests of shareholders, customers and the stability of the financial system. The research results show that OJK has a very important role in ensuring the sustainability and health of the banking sector. With its broad authority, OJK is able to respond quickly to changing market conditions and implement appropriate policies. The implications of these findings include increasing transparency, expanding cooperation with international supervisory institutions, and strengthening the role of the OJK in promoting the principles of good governance in the banking sector.